Incidence of Health-care-Associated Infections and Adherence to Prevention Strategies: A Study at a Military Hospital - Nehad Jaser Ahmed (Asian Journal of Pharmaceutics (AJP), 2025)
Background and Aim: One of the most common adverse events that occur during the provision of health-care services is health-care-associated infection (HAI). HAIs include catheter-associated urinary tract infections (CAUTI), surgical site infections (SSI), ventilator-associated pneumonia (VAP), and central line-associated bloodstream infections (CLABSI). The purpose of this study is to explore the prevalence of HAIs and assess compliance with HAI prevention strategies in a military hospital in Alkharj. Methods: The data were collected from electronic health records in addition to patient charts, microbiological laboratory reports, and admission/discharge/transfer records. The data were presented as frequencies and percentages. Results: The overall CLABSI rate was 0.91/1,000 central line days, the overall rate of CAUTI was 0.27/1,000 urinary catheter days, the overall rate of VAP was 0.49/1,000 ventilator days, and the overall SSI rate for the year was 0.15%. This study reveals a low prevalence of HAIs, including CLABSI, SSIs, CAUTI, and VAP, alongside high adherence to prevention protocols at the military hospital in Alkharj. Conclusion: The findings of the study demonstrate the effectiveness of the hospital’s infection control measures. Sustained efforts in monitoring, training, and protocol evaluation are crucial to maintaining these outcomes, serving as a model for other healthcare facilities aiming to reduce HAIs and improve patient safety.